Собрание сочинений: В 10 т. (Ильин И.А. ; сост. Лисица Ю.Т.) - Ильин Иван Александрович (1996)
Прил.: с. 287-556. - Коммент.: с.557-605 Экземпляры: КХ (20000522) / Инвентарный номер: 1034637 / Цена: 85.60 / Сис.шифр: 87.3(2) / Авт.знак: И 46 / ГРНТИ: 02 / ББК: 87.3(2)61-07